m-EASIX (better than EASIX) predicts severe CAR T-cell toxicities, worse overall survival, and discriminates cytokine release syndrome from sepsis - Moreno-Castaño, Ana Belén; Fernández, Sara; Brillembourg, Helena; Iraola, Gontzal; Moreno, David F; Ventosa-Capell, Helena; Martinez-Sanchez, Julia; De Moner, Blanca; Molina, Patricia; Ramos, Alex; Palomo, Marta; Gómez-Ramírez, Pilar; et al. (Frontiers in Immunology, 2026)
BackgroundCytokine Release Syndrome (CRS) and Immune Effector Cell-Associated Neurotoxicity Syndrome (ICANS) are life-threatening complications that often arise after CAR T-cell immunotherapy. Endothelial dysfunction is believed to play a central role in their development, leading to the interest in biomarker-based tools for diagnosis and differentiating these toxicities from sepsis. This study aimed to evaluate the Endothelial Activation Stress Index (EASIX) and its modified version (m-EASIX, which replaces creatinine with C-reactive protein [CRP] (mg/dL)) as early predictors of severe CRS and ICANS, as well as tools to distinguish CRS from sepsis.MethodsOne hundred and nineteen patients treated with CAR T-cell therapy for CD19-positive hematologic malignancies (n=94) or multiple myeloma (n=23) were included. EASIX and m-EASIX scores were measured at various time points: before CAR T-cell infusion, 24–48 hours post-infusion, at CRS or ICANS onset, and after treatment for each toxicity. A comparator group of 129 sepsis patients, including 86 with hematologic malignancies, was also analyzed.ResultsBoth EASIX and m-EASIX correlated with biomarkers of endotheliopathy, with m-EASIX showing stronger predictive power for severe toxicities and ICU admission. Higher EASIX and m-EASIX values at early time points were associated with worse overall survival (OS). Furthermore, m-EASIX accurately distinguished CRS from sepsis at symptom onset.Conclusionsm-EASIX is a practical and accessible tool for the early prediction of severe CAR T-cell-related toxicities, risk stratification, and differential diagnosis from sepsis, offering potential to guide clinical decision-making and early intervention.